Fecundity, length at maturity and gonadal development indices of river catfish (Clupisoma garua) of the old Brahmaputra River in Bangladesh - Mehedi Hasan; Md. Hafiz All Hosen; Md. Idris Miah; Zoarder Faruque Ahmed; Mousumi Sarker Chhanda; Sheik Istiak Md. Shahriar (Egyptian Journal of Aquatic Research, 2020)
The present study aims to estimate the fecundity, maturity and gonadal indices of Clupisoma garua population existing in the old Brahmaputra River, Bangladesh. The samples were collected once every month from the 1st April 2016 to the 31st March 2017 and yielded a total of 90 females and 19 males. The standard length (SL) and the body weight (BW) of females ranged from 11.8 to 27.8 cm and 23.0 to 272.2 g, respectively. The lowest value of the GSI means for females was found in November (0.22) while the highest value was in June (1.87). The scatter plot of the SL with corresponding GSI revealed that the length at maturity for females was attained in 17.1 cm of standard length. The lowest value of fecundity was 6159 and the highest was 22,166 oocytes. The relationship between BW and fecundity was F = 167.6BW – 9211 (coefficient determinant, r2 = 0.537), while the relationship between SL and fecundity was expressed as F = 0.04619SL2.177 (r2 = 0.551). Based on the GSI means, it was manifested that the possible spawning season was from May to August with a peak in June.